The Influence of Brand Trust and Brand Commitment on Brand Loyalty Eiger in Surabaya - Satria Ardhana; Rizky Dermawan (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to determine the influence of brand trust and brand commitment on the brand loyalty of Eiger in Surabaya City. The research method used is quantitative. The population in this study are people who live in the city of Surabaya, the exact number of which is not known. The sample takers used nonprobability sampling with a purposive sampling technique. With a sample of 91 respondents, namely people who have purchased at least 2 Eiger products in the city of Surabaya. Then the data was processed using Partial Least Square (PLS) data analysis techniques. The research results show that brand trust and brand commitment have a positive influence on brand loyalty Eiger in Surabaya City.